Principal empowerment policy contexts and implementation - Enriquez, Eleanor Antonieta T. (2005)
The study described the political, economic, and socio-cultural contents prior to the formulation of the Principal Empowerment Policy. It was concluded that the implementation of public school elementary principals by recognizing the provision of authority, responsibility, and accountability in relation to their administrative, instructional, and fiscal roles. It also shaped the roles of public elementary school principals by working out on different areas of school management. Lastly, it is not the organizational structure of the DepEd that makes the educational system effective, but it is how people implemented or carried out their duties.
Thesis (M.A. Educational Administration)--University of the Philippines, Diliman.
Keywords: Elementary school principals -- Philippines -- Central Luzon; School management and organization -- Philippines -- Central Luzon